#### Question

Show that `(4pq + 3q)^2 - (4pq - 3q)^2 = 48pq^2`

#### Solution

L.H.S = (4pq + 3q)^{2} - (4pq - 3q)^{2}

= (4pq)^{2} + 2(4pq)(3q) + (3q)^{2} = [(4pq)^{2} - 2(4pq)(3q) +(3q)^{2}]

= 16p^{2}q^{2} + 24pq^{2} + 9q^{2} - [16p^{2}q^{2} - 24pq^{2} + 9q^{2}]

= 16p^{2}q^{2} + 24pq^{2} + 9q2 - 16p^{2}q^{2} +24pq^{2} - 9q^{2}

= 48pq^{2} = R.H.S

Is there an error in this question or solution?

Solution Show that (4pq + 3q)Square2 - (4pq - 3q)Square2 = 48pqsquare2 Concept: Concept of Identity.